Economics of China's joint-stock co-operatives - Laixiang Sun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
In the 1990s, a new ownership form called `joint-stock co-operative' (gufen hezuozhi) became widely adopted in China's township and village enterprise sector. The promising dynamics and high adaptive ability of the new ownership form is in contradiction with the conclusions suggested by the existing literature on industrial co-operatives and other types of employee ownership. To show the adaptive efficiency feature of the new form, this paper identifies and analyses the mechanisms that are developed by China's joint-stock cooperatives to avoid excessive costs of collective decision making, to check insider control, to mobilize internal and external finances, to diversify risk, and to facilitate further evolving. By this way, the paper also sheds light on the roles that an alternative form of ownership and governance can play in an alternative institutional environment.
Keywords: D21; P13; P32; 330; joint-stock co-operatives; ownership and governance; China; Genossenschaft; Eigentümerstruktur; Corporate Governance; China